Fish behavior and its use in the capture and culture of fishes. Proceedings of the conference on the physiological and behavioral manipulation of food fish.. - Bardach, J. E.; Magnuson, John J.; May, Robert C.; and Reinhart, Jahanna M. (eds.) (ICLARM, 1980)
ICLARM Conference Proceedings; 5